Post-treatment drug use, recidivism, analogous behaviors, and perceptions of fairness: Examining whether parolees with low self-control will benefit from the Collaborative Behavioral Management intervention - Chintakrindi, Sriram (2014)
This dissertation tested Gottfredson and Hirschi's (1990) low self-control theory and its relationship with post-treatment outcomes by conducting a secondary-data analysis of a randomized controlled trial on parolees (n=569) called the Step'n Out study (2005). The Step'n Out study (2005) compared the results of a control group (standard parole) with an experimental treatment for parolees called the Collaborative Behavioral Management (CBM) intervention which was designed to improve substance-use treatment outcomes, reduce drug use, and reduce recidivism for parolees participating in the study. Low self-control theory states that individuals with character traits that are impulsive, risk-seeking, self-centered, and display volatile temper have a high likelihood of engaging in criminal and analogous (i.e. risky sexual practices) behaviors. Gottfredson and Hirschi's (1990) theory makes the assumption that these traits are the result of parental socialization practices, are not able to be changed after the age of 8 or 10, and are stable across time. In order to measure low self-control for the present study, an exploratory factor analysis was conducted on 20 self-report items collected at intake from the parolees in the study and a unidimensional measure of low self-control was constructed. Based on low self-control theory, this study hypothesizes that parolees who self-report engaging in substance use, recidivism, and analogous behaviors after the end of the treatment intervention at the 3 and 9 month follow-up periods will have low self-control traits (measured at intake). Also based on the theory, this study hypothesizes that the treatment condition (control group vs. CBM group) will not moderate the relationship between low self-control traits and post-treatment outcomes even when controlling for demographic, risk-factors, peer-associations, and treatment dosage. The exploratory results from this study were reported using univariate, bivariate, and multivariate statistics. Also a confirmatory factor analysis was conducted to measure the direct and indirect effects of low self-control, peer-associations, and perceptions of fairness on post-treatment outcomes. The results from this dissertation study largely indicate that parolees across the self-control spectrum (low to high levels of self-control) are engaging in post-treatment outcomes (substance use, recidivism, and analogous behaviors) at the 3 and 9 month follow-up periods even when controlling for age, gender, race, age at first arrest, education status, dosage levels, and treatment condition. Therefore, based on the findings from this study, low self-control theory does not allow researchers to understand the causal mechanisms by which post-treatment outcomes occur for parolees. More theoretical refinement of the theory or alternative theories are needed in order to explain the post-treatment outcomes of parolees participating in the Step'n Out study. However, a particularly interesting finding that also has strong public policy implications indicates that parolees that self-reported physically or verbally threatening someone at both the 3 and 9 month follow-up periods had statistically significant lower mean levels of self-control compared to parolees who did not physically or verbally threaten someone